Respuestas

¡La mejor respuesta!
2014-02-18T20:49:23+01:00
A) x / (-2) = 3 - x
   - x/2 = 3 - x
   - x/2 + x = 3
   x/2 = 3
   x = 3 x 2
   x = 6

b) (-10/x) + 3 = - 10 - 2
   - 10/x = - 10 - 2 - 3
   -10/x = - 15
   - 10 = - 15 x
   10 = 15 x
   10/15 = x
   2/3 = x

c) x / 3 = 2 (x - 5)
   x = 3 * 2 (x - 5)
   x = 6 (x - 5)
   x = 6 x - 30
   30 = 6 x - x
   30 = 5 x
   30/5 = x
   6 = x
2014-02-18T20:54:20+01:00
A)
x = (3 -x) * (-2)
x = -6 - 2x
x + 2x = -6
3x = -6
x = -6/3
x = -2

B) 
( -10 / x + 3) = (-10) + ( -2) 
-10 / x = -10 -2 -3
-10 / x = -15
x = 10/15
x = 2/3

C)
(x / 3) = 2 * ( x -5 )
x / 3 = 2x -10
x =6x -30
-6x + x = -30
-5x = -30
x = -30 / -5
x = 6